Protein kinetics: Structures of intermediates and reaction mechanism from time-resolved x-ray data - Schmidt, Marius (National Academy of Sciences, 2004)
We determine the number of authentic reaction intermediates in the later stages of the photocycle of photoactive yellow protein at room temperature, their atomic structures, and a consistent set of chemical kinetic mechanisms, by analysis of a set of time-dependent difference electron density maps spanning the time range from 5 μs to 100 ms. The successful fit of exponentials to right singular vectors derived from a singular value decomposition of the difference maps demonstrates that a chemical kinetic mechanism holds and that structurally distinct intermediates exist. We identify two time-independent difference maps, from which we refine the structures of the corresponding intermediates. We thus demonstrate how structures associated with intermediate states can be extracted from the experimental, time-dependent crystallographic data. Stoichiometric and structural constraints allow the exclusion of one kinetic mechanism proposed for the photocycle but retain other plausible candidate kinetic mechanisms.